Selection on Mitochondrial Variants Occurs between and within Individuals in an Expanding Invasion. (6th January 2016) - Rollins, Lee A.; Woolnough, Andrew P.; Fanson, Benjamin G.; Cummins, Michelle L.; Crowley, Tamsyn M.; Wilton, Alan N.; Sinclair, Ron; Butler, Ashleigh; Sherwin, William B.
Abstract: Mitochondria are critical for life, yet their underlying evolutionary biology is poorly understood. In particular, little is known about interaction between two levels of evolution: between individuals and within individuals (competition between cells, mitochondria or mitochondrial DNA molecules). Rapid evolution is suspected to occur frequently in mitochondrial DNA, whose maternal inheritance predisposes advantageous mutations to sweep rapidly though populations. Rapid evolution is also predicted in response to changed selection regimes after species invasion or removal of pathogens or competitors. Here, using empirical and simulated data from a model invasive bird species, we provide the first demonstration of rapid selection on the mitochondrial genome within individuals in the wild. Further, we show differences in mitochondrial DNA copy number associated with competing genetic variants, which may provide a mechanism for selection. We provide evidence for three rarely documented phenomena: selection associated with mitochondrial DNA abundance, selection on the mitochondrial control region, and contemporary selection during invasion.